Process for producing polyolefins

By using maleic anhydride copolymer to copolymerize with the main catalyst during the polyolefin production process, the reactor electrostatic, scaling and crust problems caused by metallocene catalysts are solved, and the stability of the polyolefin production process and product quality are improved.

CN119912615APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311433199.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

During the polyolefin production process, metallocene catalysts cause reactor electrostatics, scaling and crust, resulting in problems such as poor heat transfer, poor particle morphology and reactor shutdown. The use of existing antistatic agents can reduce catalyst activity and productivity.

Method used

In the presence of maleic anhydride copolymer and main catalyst, the polymerized monomer is polymerized, and the catalyst is directly added to the reactor to prevent the increase in the production cost of the catalyst, and the reactor scale is reduced or eliminated by maleic anhydride copolymer microspheres.

Benefits of technology

It is achieved to reduce or eliminate reactor scaling during the polyolefin production process, maintain catalyst activity, and obtain more polyolefins with uniform particle size.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004525476900000031
    Figure BDA0004525476900000031
  • Figure BDA0004525476900000121
    Figure BDA0004525476900000121
  • Figure BDA0004525476900000131
    Figure BDA0004525476900000131
Patent Text Reader

Abstract

The invention relates to the field of polyolefin, and discloses a method for producing polyolefin. The method includes polymerizing a polymeric monomer in the presence of a maleic anhydride copolymer and a procatalyst. According to the method used by the invention, the maleic anhydride copolymer is directly added into the reactor, so that the phenomena of scaling and the like of the reactor can be reduced or eliminated, and the negligible influence on the activity of the catalyst is realized. More polyolefin can be obtained through the method, and the particle size of the obtained polyolefin is uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polyolefins, and in particular to a method for producing polyolefins. Background Art

[0002] In the polyolefin industry, metallocene catalysts are more reactive than conventional Ziegler-Natta catalysts, and they can produce polymers with improved physical properties. However, metallocene catalysts often cause the reactor to produce phenomena such as static electricity, scaling and / or crusting, which can cause many serious problems, including poor heat transfer, poor particle morphology, etc., especially when used in fluidized bed reactors, and even cause the reactor to be forced to shut down in severe cases. In order to solve these problems, many methods have been disclosed, such as CN1178222A uses an amine substance to add an antistatic agent to control the static level of the reactor, other antistatic agents have also been used to control the scaling of the reactor, CN107406537A uses an alkylene oxide-derived polymer substance as an antistatic agent, which significantly reduces static electricity in the reactor, and the antistatic agent type used by CN113382999A is a fatty acid ester, which can reduce the phenomenon of caking in the reactor.

[0003] However, the use of some antistatic agents can lead to a decrease in catalyst productivity and greatly reduce catalyst activity. New methods are needed to control the electrostatic level of the reactor and reduce the occurrence of phenomena such as reactor fouling. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems existing in the prior art and provide a method for producing polyolefins.

[0005] In order to achieve the above object, the present invention provides a method for producing polyolefin, which comprises: polymerizing a polymerization monomer in the presence of a maleic anhydride copolymer and a main catalyst.

[0006] Through the above technical scheme, the method used in the present invention is to directly add the maleic anhydride copolymer into the reactor, the maleic anhydride copolymer is not only easy to obtain, but also can prevent the additional catalyst preparation cost, and at the same time, the maleic anhydride copolymer microspheres can reduce or eliminate the phenomenon of reactor scaling, and have a negligible effect on the activity (discharge amount) of the catalyst. More polyolefins can also be obtained through the method of the present invention, and the polyolefin particle size obtained is relatively uniform. DETAILED DESCRIPTION

[0007] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0008] The present invention provides a method for producing polyolefin (or a method for reducing agglomeration in the production process of polyolefin), which comprises: polymerizing polymerization monomers in the presence of a maleic anhydride copolymer and a main catalyst.

[0009] In the present invention, in order to further reduce or eliminate the phenomenon of reactor scaling and the like in the process of producing polyolefins and obtain more polyolefins with relatively uniform particle sizes, the amount of the maleic anhydride copolymer is 5-80wt% of the amount of the main catalyst, and can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt% or the range formed by any two of the above values ​​and the value within the range, preferably 10-70wt%, more preferably 15-60wt%.

[0010] Preferably, the main catalyst contains metal elements, and the molar ratio of the main catalyst to the polymerization monomer is 1:10-10. 8 , can be 1:10, 1:20, 1:50, 1:100, 1:10 3 , 1:10 4 , 1:10 5 , 1:10 6 , 1:10 7 Or the range formed by any two of the above values ​​and the value within the range, more preferably 1:20-10 7 .

[0011] In the present invention, the main catalyst is not limited, and can catalyze the polymerization of monomers to generate polyolefins. The main catalyst includes a Ziegler-Natta catalyst and / or a metallocene catalyst.

[0012] Preferably, the metallocene catalyst is a supported bridged metallocene catalyst.

[0013] In the present invention, the supported bridged metallocene catalyst comprises: a bridged metallocene compound, a first co-catalyst and a carrier.

[0014] In the present invention, the bridged metallocene compound is: CpXCpMQ2, wherein Cp is a metallocene ligand selected from a cyclopentadiene derivative group, wherein the cyclopentadiene derivative group includes a cyclopentadienyl group, an indenyl group or a fluorenyl group, and the cyclopentadiene derivative group in the ligand may contain at least one substituent, wherein the substituent is selected from a C1-C12 alkyl group, an alkoxy group, a silane group, an aryl group or an aralkyloxy group, preferably a methyl group, an ethyl group, a propyl group or a butyl group, more preferably an isopropyl group or an isobutyl group; X is a bridging group, which may be a substituted alkyl group or a cycloalkyl group. A C1-C4 carbon bridge, a silicon bridge or a germanium bridge, preferably, the general formula of X is R1R2Y, wherein Y is an element C, Si or germanium, R1 and R2 are the same or different, and are alkyl or aryl, such as CH3, CH2CH3, etc.; or X is a C1-C4 alkylene group, such as CH2CH2, CH2CH2CH2, CH2CH2CH2CH2; M is selected from any one of the elements of Group IVB in the periodic table, preferably Zr or Ti, more preferably Zr; Q is selected from halogen, preferably chlorine.

[0015] In the present invention, the first co-catalyst is aluminoxane having the following general structural formula:

[0016] Wherein, R represents a C1-C12 hydrocarbon group, preferably a methyl group; R2 represents an alkyl group or an aryl group; a represents an integer of 4-30, preferably an integer of 10-30.

[0017] In the present invention, the carrier is not limited and can be used to load the bridged metallocene compound and the first co-catalyst. Preferably, the carrier is silica gel.

[0018] In the present invention, the molar ratio of the metallocene compound to the first cocatalyst is 0.0001-0.1:1, preferably 0.002-0.05:1, more preferably 0.005-0.03:1. The mass ratio of the first cocatalyst to the carrier is 1:0.5-4, preferably 1:1-2.

[0019] In the present invention, the preparation of the supported bridged metallocene catalyst includes: firstly loading the first cocatalyst on a carrier to obtain the first cocatalyst loaded on the carrier, and then loading the bridged metallocene compound on the first cocatalyst loaded on the carrier. The specific preparation method can be found in CN103087241A.

[0020] In the present invention, in order to further reduce or eliminate the phenomenon of reactor fouling and the like in the process of producing polyolefins and obtain more polyolefins with relatively uniform particle sizes, a co-catalyst is added during the polymerization process. Preferably, the co-catalyst may be an alkyl aluminum, more preferably at least one of triethyl aluminum, triisobutyl aluminum and tri-n-butyl aluminum. Preferably, the co-catalyst contains metal elements. The molar ratio of the main catalyst to the co-catalyst is 1:10-5000, calculated as the metal elements, and can be 1:10, 1:20, 1:50, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, 1:1000, 1:1500, 1:2000, 1:2500, 1:3000, 1:3500, 1:4000, 1:4500, 1:5000 or the range formed by any two of the above values ​​and the values ​​within the range, preferably 1:20-1000.

[0021] In the present invention, in order to further reduce or eliminate the phenomenon of reactor scaling and the like in the process of producing polyolefins and obtain more polyolefins with relatively uniform particle sizes, the content of the structural unit provided by maleic anhydride in the maleic anhydride copolymer is 45-65 mol%, which can be 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol% or the range formed by any two of the above values ​​and the values ​​within the range. Preferably, the average particle size of the maleic anhydride copolymer is 300-1500 nm, which can be 300 nm, 500 nm, 700 nm, 900 nm, 1100 nm, 1300 nm, 1500 nm or the range formed by any two of the above values ​​and the values ​​within the range. More preferably, the weight average molecular weight of the maleic anhydride copolymer is 5000-60000, and can be 5000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000 or a range formed by any two of the above values ​​or a value within the range.

[0022] In the present invention, the maleic anhydride copolymer is not limited and is a common maleic anhydride copolymer in the art. The maleic anhydride copolymer includes structural units provided by maleic anhydride and other structural units, and the other structural units are selected from copolymer structural units provided by C4-C12 olefins and / or structural units provided by vinyl acetate; preferably, the C4-C10 olefin is selected from one of 1-butene, isobutylene, isoprene, octene, pentene, hexene, styrene, α-methylstyrene and vinyl acetate.

[0023] Preferably, the maleic anhydride copolymer is a copolymer of at least two components; more preferably, the maleic anhydride copolymer is a terpolymer, and one of the other structural units accounts for 10-90 mol% of the other structural units, which can be 10 mol%, 20 mol%, 30 mol%, 40 mol%, 50 mol%, 60 mol%, 70 mol%, 80 mol%, 90 mol% or the range formed by any two of the above values ​​and the value within the range.

[0024] Preferably, the maleic anhydride copolymer is selected from at least one of maleic anhydride-α-methylstyrene copolymer, maleic anhydride-vinyl acetate copolymer, maleic anhydride-1-butene copolymer, maleic anhydride-isoprene copolymer, maleic anhydride-octene copolymer, maleic anhydride-pentene copolymer, maleic anhydride-isobutylene copolymer, maleic anhydride-hexene copolymer, maleic anhydride-styrene copolymer, maleic anhydride-α-methylstyrene-styrene copolymer and maleic anhydride-vinyl acetate-α-methylstyrene copolymer.

[0025] Further preferably, in the maleic anhydride-vinyl acetate-α-methylstyrene copolymer, the content of the structural unit provided by the vinyl acetate is 5-30 mol%, the content of the structural unit provided by α-methylstyrene is 20-45 mol%, and the sum of the contents of each structural unit in the copolymer is 100 mol%.

[0026] In the present invention, in order to better carry out the polymerization reaction and obtain a polyolefin product with better performance, the polymerization monomer is ethylene and an optional α-olefin. More preferably, the polymerization monomer is ethylene and an α-olefin, and the weight ratio of ethylene to the α-olefin is 1:0.01-0.5, which can be 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5 or the range formed by any two of the above values ​​and the value within the range, more preferably 1:0.01-0.35; preferably, the α-olefin is selected from at least one of propylene, 1-butene, 1-pentene, 1-hexene and 1-octene.

[0027] In the present invention, in order to better carry out the polymerization reaction and obtain a polyolefin product with better performance, the polymerization conditions include: a temperature of 0-150°C, which can be 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or a range formed by any two of the above values ​​and a value within the range; a pressure of 0.1-10MPa, which can be 0.1MPa, 0.5MPa, Pa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa, 3.5MPa, 4MPa, 4.5MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa or the range formed by any two of the above values ​​and the values ​​within the range, the time is 0.5-5h, and can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or the range formed by any two of the above values ​​and the values ​​within the range.

[0028] In the present invention, the polymerization method is not limited, and is a common polyolefin polymerization method in the art. Preferably, the polymerization method is selected from a gas phase method or a slurry method.

[0029] In the present invention, in order to better carry out the polymerization reaction and obtain a polyolefin product with better performance, in the slurry method, the polymerization conditions include: temperature of 0-130°C, preferably 10-90°C; pressure of 0.1-10MPa, preferably 0.5-2MPa; time of 0.5-5h, preferably 0.5-3h; preferably, in the slurry method, the polymerization medium is an organic solvent, preferably at least one of alkanes, cycloalkanes and aromatics, more preferably hexane and / or isobutane. Preferably, a certain amount of co-catalyst is added to the reaction medium during the polymerization process to remove impurities.

[0030] In the present invention, in order to better carry out the polymerization reaction and thus obtain a polyolefin product with better performance, in the gas phase method, the polymerization conditions include: temperature of 30-150°C, preferably 50-110°C, pressure of 0.5-3.0MPa, preferably 0.5-2.5MPa, reaction time of 0.5-5h, preferably 0.5-3h.

[0031] In the present invention, the polymerization medium in the gas phase method is not limited as long as it does not affect the polymerization reaction. Preferably, the polymerization medium in the gas phase method is nitrogen and / or an inert gas, more preferably nitrogen.

[0032] In the present invention, the polymerization reaction can also be carried out in the presence of hydrogen to adjust the molecular weight of the obtained polyolefin, wherein the molar ratio of the polymerization monomer to hydrogen is 1:0.0001-10, more preferably 1:0.001-3.

[0033] The present invention also relates to the use of the maleic anhydride copolymer in reducing scaling in the polyolefin production process and / or improving the product uniformity of the polyolefin.

[0034] The present invention will be described in detail below through examples. In the following examples, ethylene: polymerization grade, Beijing Huanyu Jinghui Jingcheng Gas Technology Co., Ltd.;

[0035] 1-Butene: polymerization grade, Beijing Huanyu Jinghui Jingcheng Gas Technology Co., Ltd.;

[0036] Hexane: n-hexane, analytical grade, Bio-Chemical;

[0037] Catalyst: supported bridged metallocene catalyst, synthesis details refer to Example 1 and Example 2 of CN103087241B;

[0038] The preparation method of maleic anhydride-styrene copolymer microspheres is shown in Example 1 of CN114426617A, wherein the content of maleic anhydride structural units is 49 mol%, the content of styrene structural units is 51 mol%, the weight average molecular weight is 40000, and the average particle size is 1100 nm;

[0039] The preparation method of maleic anhydride-isobutylene copolymer microspheres is shown in Example 1 of CN116262803A, wherein the content of maleic anhydride structural units is 49 mol%, the content of isobutylene structural units is 51 mol%, the weight average molecular weight is 35000, and the average particle size is 1300 nm;

[0040] The preparation method of maleic anhydride-hexene copolymer microspheres is shown in Example 1 of CN114426639A, wherein the content of maleic anhydride structural units is 49 mol%, the content of isobutylene structural units is 51 mol%, the weight average molecular weight is 38000, and the average particle size is 1600 nm;

[0041] The preparation method of maleic anhydride-isoprene copolymer microspheres is shown in Example 1 of CN116262802A, wherein the content of maleic anhydride structural units is 50 mol%, the content of isobutylene structural units is 50 mol%, the weight average molecular weight is 34000, and the average particle size is 1270 nm;

[0042] The preparation method of maleic anhydride-vinyl acetate-α-methylstyrene copolymer microspheres is shown in Example 1 of CN 112708020B, wherein the content of maleic anhydride structural unit is 51 mol%, the content of vinyl acetate structural unit is 30 mol%, the content of α-methylstyrene structural unit is 19 mol%, the weight average molecular weight is 51000, and the average particle size is 1400 nm;

[0043] The preparation method of maleic anhydride-styrene-α-methylstyrene copolymer microspheres is shown in Example 1 of CN 112708018A, wherein the content of maleic anhydride structural unit is 50 mol%, the content of styrene structural unit is 10 mol%, the content of α-methylstyrene structural unit is 40 mol%, the weight average molecular weight is 48000, and the average particle size is 1200 nm;

[0044] Preparation method of maleic anhydride-n-octadecene copolymer microspheres: According to the method of Example 1 of CN114426639A, hexene is replaced by n-octadecane, the content of structural units provided by maleic anhydride is 49 mol%, the content of structural units provided by n-octadecene is 51 mol%, the weight average molecular weight is 41000, and the average particle size is 1350 nm;

[0045] Unless otherwise specified, the pressures described in the present invention refer to gauge pressures.

[0046] The following analytical test methods were used in the following examples and comparative examples:

[0047] Density (D): Determined according to GBT 1033.2-2010, density gradient column method.

[0048] Melt Flow Rate (MFR): measured according to GB / T 3682-2000ASTM D1238 at 190°C and a load of 2.16 kg.

[0049] Screening: The analysis was performed using the ANALYSETTE 3SPARTAN analyzer from FRITSCH with an amplitude of 2.0 mm and a vibration time of 15 min.

[0050] Example 1

[0051] Polymerization of ethylene: The polymerization reaction of ethylene was carried out in a 10L autoclave reactor. Before adding the materials, the dehydrated and deoxygenated polymerization autoclave was purged with nitrogen for at least 3 times, and then 5L of hexane dried by molecular sieve and nitrogen-bubbled was injected. After the temperature was raised to 50°C, 0.14mol of triisobutylaluminum, a metallocene catalyst (30mg) with a Zr content of 0.28mmol, and 5mL of hexane slurry of maleic anhydride-styrene copolymer microspheres were added in sequence. The concentration of the maleic anhydride-styrene copolymer microsphere slurry was 2g / L. Finally, 1L of hexane was added to flush the catalyst pipeline, and the reactor was heated again. After the temperature was raised to 60°C, ethylene (18mol) was continuously added to make the ethylene partial pressure 0.7MPa, and the reaction was carried out at constant pressure for 2 hours. After the polymerization was completed, the reactor was cooled to room temperature and vented, and the polymer powder was separated from the hexane.

[0052] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.84 dg / min and a density of 0.946 g / ml. There is no accumulation of polymer in the device system, the particle size of the prepared polyethylene is uniform (particle size distribution is shown in Table 1), and there is no clogging or scaling in the reactor or other equipment.

[0053] Example 2

[0054] Polymerization of ethylene: The polymerization reaction of ethylene is carried out in a fluidized bed reactor. Before adding materials, the polymerization kettle that has been dehydrated and deoxygenated is purged with nitrogen for at least 3 times, and then the temperature is raised to 50°C, and 0.28mmol (Zr content) of metallocene catalyst (30mg) is added, and 10mg of maleic anhydride-isobutylene copolymer microspheres are added. The reactor is heated again, and after the temperature is raised to 60°C, ethylene (18mol) is continuously added at a pressure of 0.7MPa. The reaction is carried out for 2 hours. After the polymerization is completed, a polymer powder is obtained.

[0055] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.86 dg / min and a density of 0.942 g / ml. There is no accumulation of polymer in the device system, the particle size of the prepared polyethylene is uniform (see Table 1 for particle size distribution), and there is no clogging or scaling in the reactor or other equipment.

[0056] Example 3

[0057] The method of Example 1 is followed, except that the maleic anhydride-styrene copolymer is replaced by a maleic anhydride-hexene copolymer.

[0058] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.82 dg / min and a density of 0.946 g / ml. There is no accumulation of polymer in the device system, the particle size of the prepared polyethylene is uniform (particle size distribution is shown in Table 1), and there is no clogging or scaling in the reactor or other equipment.

[0059] Example 4

[0060] The method of Example 1 is followed, except that the maleic anhydride-styrene copolymer is replaced by maleic anhydride-vinyl acetate-α-methylstyrene copolymer.

[0061] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.88 dg / min and a density of 0.946 g / ml. There is no accumulation of polymer in the device system, the particle size of the prepared polyethylene is uniform (particle size distribution is shown in Table 1), and there is no clogging or scaling in the reactor or other equipment.

[0062] Example 5

[0063] The method of Example 1 is followed, except that the maleic anhydride-styrene copolymer is replaced by a maleic anhydride-styrene-α-methylstyrene copolymer.

[0064] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.88 dg / min and a density of 0.946 g / ml. There is no accumulation of polymer in the device system, the particle size of the prepared polyethylene is uniform (particle size distribution is shown in Table 1), and there is no clogging or scaling in the reactor or other equipment.

[0065] Example 6

[0066] The method of Example 1 was followed, except that ethylene was replaced with ethylene and 1-butene, and the weight ratio of ethylene to 1-butene was 1:0.03. At the same time, the maleic anhydride-styrene copolymer microspheres were replaced with maleic anhydride-isoprene copolymer microspheres.

[0067] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.62 dg / min and a density of 0.934 g / ml. There is no accumulation of polymer in the device system, the particle size of the prepared polyethylene is uniform (particle size distribution is shown in Table 1), and there is no clogging or scaling in the reactor or other equipment.

[0068] Example 7

[0069] Polymerization of ethylene: The polymerization reaction of ethylene was carried out in a 10L autoclave reactor. Before adding the materials, the dehydrated and deoxygenated polymerization autoclave was purged with nitrogen for at least 3 times, and then 5L of hexane dried by molecular sieve and nitrogen-bubbled was injected. After the temperature was raised to 60°C, 0.07mol of triisobutylaluminum, 0.28mmol (Zr content) of metallocene catalyst (30mg) and 6mL of hexane slurry of maleic anhydride-styrene copolymer microspheres were added in sequence. The concentration of the maleic anhydride-styrene copolymer microsphere slurry was 2g / L. Finally, 1L of hexane was added to flush the catalyst pipeline, and the reactor was heated again. After the temperature was raised to 70°C, ethylene (19mol) was continuously added to make the ethylene partial pressure 0.6MPa. The reaction was carried out at constant pressure for 2 hours. After the polymerization was completed, the reactor was cooled to room temperature and vented to separate the polymer powder from the hexane.

[0070] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.81 dg / min and a density of 0.945 g / ml. There is no accumulation of polymer in the device system, the particle size of the prepared polyethylene is uniform (particle size distribution is shown in Table 1), and there is no clogging or scaling in the reactor or other equipment.

[0071] Example 8

[0072] Polymerization of ethylene: The polymerization reaction of ethylene was carried out in a 10L autoclave reactor. Before adding the materials, the dehydrated and deoxygenated polymerization autoclave was purged with nitrogen for at least 3 times, and then 5L of hexane dried by molecular sieve and nitrogen-bubbled was injected. After the temperature was raised to 40°C, 0.14mol of triisobutylaluminum, 0.28mmol (Zr content) of metallocene catalyst (30mg), 6mL of hexane slurry of maleic anhydride-styrene copolymer microspheres were added in sequence, and the concentration of maleic anhydride-styrene copolymer microspheres slurry was 2g / L. Finally, 1L of hexane was added to flush the catalyst pipeline, and the reactor was heated again. After the temperature was raised to 50°C, ethylene (16mol) was continuously added to make the ethylene partial pressure 0.8MPa, and the reaction was carried out at constant pressure for 2 hours. After the polymerization was completed, the reactor was cooled to room temperature and vented, and the polymer powder was separated from the hexane.

[0073] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.69 dg / min and a density of 0.946 g / ml. There is no accumulation of polymer in the device system, the particle size of the prepared polyethylene is uniform (particle size distribution is shown in Table 1), and there is no clogging or scaling in the reactor or other equipment.

[0074] Example 9

[0075] The method of Example 1 was followed, except that the amount of maleic anhydride-styrene copolymer microsphere slurry added was 1.5 mL.

[0076] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.81 dg / min and a density of 0.946 g / ml. There is almost no accumulation of polymer in the device system. The particle size of the prepared polyethylene is relatively uniform (particle size distribution is shown in Table 1). When the reactor is disassembled, it is found that 15g of powder is adhered to the inner wall of the reactor.

[0077] Example 10

[0078] The method of Example 1 is followed, except that the maleic anhydride-styrene copolymer is replaced with maleic anhydride-n-octadecene.

[0079] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.81 dg / min and a density of 0.946 g / ml. A small amount of polymer is accumulated in the device system. The particle size of the prepared polyethylene is relatively uniform (particle size distribution is shown in Table 1). When the reactor is disassembled, it is found that 25g of powder is adhered to the inner wall of the reactor.

[0080] Comparative Example 1

[0081] The method of Example 1 was followed, except that the hexane slurry of maleic anhydride-styrene copolymer microspheres was not added.

[0082] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.85 dg / min and a density of 0.948 g / ml. There is a small amount of polymer accumulation in the device system. The particle size of the prepared polyethylene is relatively uniform (particle size distribution is shown in Table 1). 58 g of powder was found to be sticking to the inner wall of the device system.

[0083] Comparative Example 2

[0084] The method of Example 1 was followed, except that the maleic anhydride copolymer microspheres were replaced with antistatic agent atmer163.

[0085] Results: The amount of polymer produced is shown in Table 1. The produced polymer has a melt index of 0.81 dg / min and a density of 0.946 g / ml. There is a small amount of polymer accumulation in the device system. The particle size of the prepared polyethylene is relatively uniform (particle size distribution is shown in Table 1). 22g of powder was found to stick to the wall in the device system.

[0086] Table 1

[0087]

[0088]

[0089] Note: The data are obtained by sieving the products from sieve hole diameters of 2mm, 1mm, 0.5mm, 0.36mm, 0.25mm, 0.18mm, and 0.07mm in sequence. 2mm represents a particle size higher than 2mm, 1mm represents a particle size of 1-2mm, 0.5mm represents a particle size of 0.5-1mm, and so on.

[0090] It can be seen from the above results that, by using the method of the present invention, there is no accumulation of polymer in the device system, no blockage or scaling in the reactor or other equipment, and more polymer can be obtained, and the particle size of the obtained polymer is also relatively uniform.

[0091] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for producing polyolefins, characterized in that The method comprises: polymerizing a polymerization monomer in the presence of a maleic anhydride copolymer and a main catalyst.

2. The method according to claim 1, wherein: The amount of the maleic anhydride copolymer is 5-80wt% of the amount of the main catalyst, preferably 10-70wt%, more preferably 15-60wt%; Preferably, the main catalyst contains metal elements, and the molar ratio of the main catalyst to the polymerization monomer is 1:10-10. 8 , more preferably 1:20-10 7 .

3. The method according to claim 2, wherein: The polymerization system also includes a co-catalyst; Preferably, the co-catalyst contains metal elements, and the molar ratio of the main catalyst to the co-catalyst is 1:10-5000, preferably 1:20-1000, calculated as metal elements.

4. The method according to claim 2 or 3, wherein: The main catalyst includes a Ziegler-Natta catalyst and / or a metallocene catalyst; Preferably, the metallocene catalyst is a supported bridged metallocene catalyst; Preferably, the co-catalyst is an alkyl aluminum.

5. The method according to claim 1 or 2, wherein: In the maleic anhydride copolymer, the content of the structural unit provided by maleic anhydride is 45-65 mol%; And / or, the weight average molecular weight of the maleic anhydride copolymer is 5000-60000; And / or, the average particle size of the maleic anhydride copolymer is 300-1500 nm; And / or, the maleic anhydride copolymer comprises structural units provided by maleic anhydride and other structural units, and the other structural units are selected from copolymer structural units provided by C4-C12 olefins and / or structural units provided by vinyl acetate; Preferably, the other structural units are provided by at least one of 1-butene, isobutylene, isoprene, octene, pentene, hexene, styrene, α-methylstyrene and vinyl acetate; Preferably, the maleic anhydride copolymer is at least a binary copolymer; Preferably, the maleic anhydride copolymer is a terpolymer, and one of the other structural units accounts for 10-90 mol% of the other structural units; Preferably, the maleic anhydride copolymer is selected from at least one of maleic anhydride-α-methylstyrene copolymer, maleic anhydride-vinyl acetate copolymer, maleic anhydride-1-butene copolymer, maleic anhydride-isoprene copolymer, maleic anhydride-octene copolymer, maleic anhydride-pentene copolymer, maleic anhydride-isobutylene copolymer, maleic anhydride-hexene copolymer, maleic anhydride-styrene copolymer, maleic anhydride-α-methylstyrene-styrene copolymer and maleic anhydride-vinyl acetate-α-methylstyrene copolymer; Preferably, in the maleic anhydride-vinyl acetate-α-methylstyrene copolymer, the content of the structural unit provided by the vinyl acetate is 5-30 mol%, the content of the structural unit provided by α-methylstyrene is 20-45 mol%, and the sum of the contents of each structural unit in the copolymer is 100 mol%.

6. The method according to claim 1 or 2, wherein: The polymerizable monomers are ethylene and optionally α-olefins.

7. The method according to claim 6, wherein: The polymerizable monomers are ethylene and α-olefin, and the weight ratio of ethylene to α-olefin is 1:0.01-0.5, more preferably 1:0.01-0.35; Preferably, the α-olefin is selected from at least one of propylene, 1-butene, 1-pentene, 1-hexene and 1-octene.

8. The method according to claim 1 or 2, wherein: The polymerization conditions include: temperature of 0-150°C, pressure of 0.1-10MPa, and time of 0.5-5h; Preferably, the polymerization method is selected from one of a gas phase method, a slurry method and a bulk method, preferably a gas phase method or a slurry method.

9. The method according to claim 8, wherein: In the slurry method, the polymerization conditions include: temperature of 0-130°C, preferably 10-90°C; pressure of 0.1-10MPa, preferably 0.5-2MPa; time of 0.5-5h, preferably 0.5-3h; And / or, in the slurry process, the polymerization medium is an organic solvent, preferably at least one of alkanes, cycloalkanes and aromatic hydrocarbons, more preferably n-hexane and / or isobutane.

10. The method according to claim 8, wherein: In the gas phase method, the polymerization conditions include: temperature of 30-150° C., preferably 50-110° C., pressure of 0.5-3 MPa, preferably 0.5-2.5 MPa, time of 0.5-5 h, preferably 0.5-3 h.